New politics 2.0 multiracial and moderate Malaysian democracy - Saifuddin Abdullah (Politics and civil society series, 2017)
This book discussed the 'how'. New politics is a perjuangan (struggle), a holistic process of doing better politics based on values and bringing our politics to a higher level where our democracy becomes mature. We need to push for further democratisation. We must end 'politics of race' with religious undertone, come up with a new multiracial political thought and realise the true meaning of moderation. We need to replace the old political configuration-'consociationalism', which is race based, with a new and better political configuration-'centripetalism', which is multiracial and moderate.